2008
DOI: 10.1111/j.1538-7836.2007.02812.x
|View full text |Cite
|
Sign up to set email alerts
|

The Residual Platelet Aggregation after Deployment of Intracoronary Stent (PREDICT) score

Abstract: The PREDICT score provides a good tool to estimate residual platelet activity after clopidogrel LD by easily available patient details. Additionally, we demonstrate its association with short-term outcome. Thus, patients with a high score may benefit from intensified antiplatelet therapy by improved platelet inhibition and risk reduction for thromboischemic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(153 citation statements)
references
References 45 publications
8
137
2
6
Order By: Relevance
“…These include CYP2C19 singlenucleotide polymorphisms, age, body mass index, diabetes mellitus, renal function, C-reactive protein, fibrinogen, and endothelial function. 18,[21][22][23][24][25][26] In this study, we simultaneously measured peripheral endothelial function by RHI and evaluated RPR in a population lacking CYP2C19*2 or *3 loss-offunction allele, selected specifically to avoid the effects of this gene on platelet activity. The results identified peripheral endothelial dysfunction as a significant determinant of high RPR in patients with stable CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include CYP2C19 singlenucleotide polymorphisms, age, body mass index, diabetes mellitus, renal function, C-reactive protein, fibrinogen, and endothelial function. 18,[21][22][23][24][25][26] In this study, we simultaneously measured peripheral endothelial function by RHI and evaluated RPR in a population lacking CYP2C19*2 or *3 loss-offunction allele, selected specifically to avoid the effects of this gene on platelet activity. The results identified peripheral endothelial dysfunction as a significant determinant of high RPR in patients with stable CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariable linear regression model consisted of RHI and the variables (age, diabetes mellitus, estimated glomerular filtration rate, and Log 10 [BNP]) that had been independently shown to impact RPR in the previous studies. 18,[21][22][23][24][25][26] Each of RHI and BNP was shown as the independently associated factor for RPR (Table 2). We also analyzed the association in the 2 groups regarding the duration of clopidogrel treatment: the short-term loading group (≤7 days) and the long-term group (>7 days).…”
Section: Correlation Between Rhi and Prumentioning
confidence: 99%
“…44 Similarly, ADP-induced P2Y 12 receptor assessed by various techniques was correlated with stent thrombosis and longterm post-PCI ischemic event occurrences and bleeding (Table 1). 32,44,45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Some studies used receiver operating characteristic curve analysis to define an optimal cutoff of on-treatment platelet reactivity for predicting thrombotic risk. In 2010, a consensus statement proposed cutoff values based on receiver operating characteristic curve analysis for different platelet function assays to be used in future studies of personalized antiplatelet therapy.…”
Section: Relation Of Ex Vivo Platelet Function Measurement To Clinicamentioning
confidence: 99%
“…Along this line, recent studies have suggested that adding clinical variables and genotype to platelet reactivity measurements (combined risk factor) will improve risk prediction. 13,68 Finally, 2 important facts should be remembered. First, the development of all antiplatelet agents has been based on an ex vivo assessment of platelet inhibition.…”
Section: Limitations Of Diagnostic Test Statistics To Describe Prognomentioning
confidence: 99%